2023
DOI: 10.1038/s41598-022-27276-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of interferon-induced protein with tetratricopeptide repeats 3 (IFIT3) in Alzheimer's disease and HIV-1 associated neurocognitive disorders

Abstract: The United Nations projects that one in every six people will be over the age of 65 by the year 2050. With a rapidly aging population, the risk of Alzheimer's disease (AD) becomes a major concern. AD is a multifactorial disease that involves neurodegeneration in the brain with mild dementia and deficits in memory and other cognitive domains. Additionally, it has been established that individuals with Human Immunodeficiency Virus-1 (HIV-1) experience a 5 to 10-year accelerated aging and an increased risk of dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Whereas IR genes are generally known to be upregulated in acute infections, their expression remains elevated in brains with HIV-associated neurocognitive disorders. 56 Their downregulation is thus noteworthy in the context of a viral illness, especially since it is associated with worse prognosis ( Figure 3 B). This downregulation has been observed in post-mortem AD brains 56 and in microglia from chronically stressed mice.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Whereas IR genes are generally known to be upregulated in acute infections, their expression remains elevated in brains with HIV-associated neurocognitive disorders. 56 Their downregulation is thus noteworthy in the context of a viral illness, especially since it is associated with worse prognosis ( Figure 3 B). This downregulation has been observed in post-mortem AD brains 56 and in microglia from chronically stressed mice.…”
Section: Discussionmentioning
confidence: 97%
“… 56 Their downregulation is thus noteworthy in the context of a viral illness, especially since it is associated with worse prognosis ( Figure 3 B). This downregulation has been observed in post-mortem AD brains 56 and in microglia from chronically stressed mice. 57 PASC-CI models may need to consider incorporating both viral infection and chronic stress, even though the prevalence for diagnosed mood disorders in our PASC-CI cohort is low ( Table S1 ).…”
Section: Discussionmentioning
confidence: 97%
“…In the context of neurodegeneration, the impairment of the proteasomal system can lead to the accumulation of protein aggregates, a hallmark of several neurodegenerative conditions such as Alzheimer's and Parkinson's disease [58]. The intricate balance of protein synthesis and degradation, as indicated by terms like post-translational protein modification regulation of the cellular amino acid metabolic process, further underscores the critical role of protein homeostasis in preventing neurodegeneration [56,60,62]. The Wnt signaling pathway was also highlighted in the yellow module.…”
Section: Implications Of Mitochondrial Dysfunction and Protein Aggreg...mentioning
confidence: 99%
“…The prevalence of HIV‐associated neurocognitive disorders (HAND) in PLWH ranges from 19% to 52% in developed countries (Atashili et al., 2013 ; Lawler et al., 2010 ), and 14% to 64% in developing countries (Debalkie Animut et al., 2019 ; Lawler et al., 2010 ). Accumulating evidence suggests that common pathways and factors are modulated in the brains of HIV + and Alzheimer's disease (AD) patients, thus pointing out similarities and convergence of these two pathologies (Achim et al., 2009 ; Chai et al., 2017 ; Esiri et al., 1998 ; Garces et al., 2023 ; Gelman & Schuenke, 2004 ; Gonzalez et al., 2023 ; Green et al., 2005 ; Izycka‐Swieszewska et al., 2000 ; Kim et al., 2013 ; Meehan et al., 2023 ; Nebuloni et al., 2001 ; Raja et al., 1997 ; Stern et al., 2018 ; Xu & Ikezu, 2009 ). As regards the development of Alzheimer's‐like pathology in older HIV + survivors, it remains unclear whether the disease develops independently or as a comorbidity of HIV‐1.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there are conflicting reports demonstrating no correlation between the levels of cerebrospinal fluid (CSF) Amyloid beta (Aβ 42) and the deposition of fibrillary brain amyloids assessed by magnetic resonance imaging (MRI) using Pittsburgh Compound B, in HIV‐infected‐individuals with HAND (Ances et al., 2012 , 2010 ; Clifford et al., 2009 ). Despite this discrepancy in the field, several studies have reported deposition of diffused amyloid depositions in the brains of HAND patients in the post‐cART era and the development of Alzheimer's‐like pathology (Achim et al., 2009 ; Chai et al., 2017 ; Esiri et al., 1998 ; Fields et al., 2020 ; Garces et al., 2023 ; Gelman & Schuenke, 2004 ; Gonzalez et al., 2023 ; Howdle et al., 2020 ; Izycka‐Swieszewska et al., 2000 ; Kim et al., 2013 ; Meehan et al., 2023 ; Nebuloni et al., 2001 ; Raja et al., 1997 ; Stern et al., 2018 ; Xu & Ikezu, 2009 ). There are reports demonstrating that HIV‐1 infected people on anti‐retrovirals, specifically, protease inhibitors, had higher amounts of neurotoxic amyloids and phospho Tau (pTau) levels in the CSF (Fields et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%